2020
DOI: 10.31566/arts.3.011
|View full text |Cite
|
Sign up to set email alerts
|

What S in a Name Experiment on the Aesthetic Judgments of Art Produced by Artificial Intelligence

Abstract: We conducted an experiment to explore the effect on aesthetic judgments influenced by the presence and awareness of the title of the abstract paintings produced by Artificial Intelligence. Fiftytwo participants (52 students from the Faculty of Fine Arts) were randomly signed into control and experimental groups. Participants of the control group were asked to rate five abstract paintings created by various artists, while the experimental group also rated the same paintings only differing in the names of the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Here, we not only wanted to attempt to replicate this finding, but also to determine whether evaluations of different painting types (representational and abstract) differ as a function of whether the purported creator was a human or AI. Research on AI-art perceptions have primarily used abstract paintings as stimuli, which could limit our understanding of the true role of painting type in aesthetic judgements (Israfilzade, 2020;Chiarella, 2022). However, Chamberlain et al (2018) presented varied painting types but found no interaction between painting creator and painting type on general aesthetic value ratings; with our extension of rating criteria, potentially different processes of judgements that may rely both on painting type and creator could be illuminated.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Here, we not only wanted to attempt to replicate this finding, but also to determine whether evaluations of different painting types (representational and abstract) differ as a function of whether the purported creator was a human or AI. Research on AI-art perceptions have primarily used abstract paintings as stimuli, which could limit our understanding of the true role of painting type in aesthetic judgements (Israfilzade, 2020;Chiarella, 2022). However, Chamberlain et al (2018) presented varied painting types but found no interaction between painting creator and painting type on general aesthetic value ratings; with our extension of rating criteria, potentially different processes of judgements that may rely both on painting type and creator could be illuminated.…”
Section: Methodsmentioning
confidence: 92%
“…Results of this study indicated that participants tended to prefer the painting that was labeled "human-created" relative to the painting labeled "AI-created." Critically, however, other studies have yielded results that are at odds with those from the aforementioned studies, finding little-to-no differences in evaluations of human-and AI-created artworks (Israfilzade, 2020;Hong & Curran, 2019;Xu et al, 2020). Additionally, though not an explicit investigation of aesthetic-judgements, per se, one study found that participants were equally likely to consider hypothetical products created by human and AI artists' as "art" (Mikalonytė & Kneer, 2022).…”
Section: Introductionmentioning
confidence: 89%
“…However, participants (non-experts) in study 1 showed no bias against AI-generated paintings. One explanation was that the label "AI-generated" might make observers feel novel (Israfilzade, 2020). Israfilzade (2020) found that abstract paintings were rated more novel and surprising when artificial intelligence accompanied the title, and no difference was found in terms of complexity, interestingness, and ambiguity arousal of the paintings.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation was that the label "AI-generated" might make observers feel novel (Israfilzade, 2020). Israfilzade (2020) found that abstract paintings were rated more novel and surprising when artificial intelligence accompanied the title, and no difference was found in terms of complexity, interestingness, and ambiguity arousal of the paintings. Moreover, participants in study 1 showed a preference for AI-generated Chinese-style to AI-generated Western-style paintings, in line with the uncertainty-identity hypothesis (Mastandrea et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of the Internet, the increase of big data, the explosive growth of computer science, and the enormous advancements in robotics and programming have resulted in the development of Artificial Intelligence, which enables it to handle complicated difficulties and tasks. Additionally, this technology appears to generate a variety of various types of content, including dialogues, music, poetry, artwork, film or news scripts, jokes, and creative problem-solving (Israfilzade & Pilelienė, 2018;Akerkar, 2019;Israfilzade, 2020). Latest developments in artificial intelligence have strengthened the effectiveness of powerful tactics such as machine learning and deep neural networks (Wang & Yuan, 2016;Hori et al, 2019;Hussain, Ameri Sianaki & Ababneh, 2019).…”
Section: Introductionmentioning
confidence: 99%